Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1083/jcb.200206015
|View full text |Cite
|
Sign up to set email alerts
|

ARFGAP1 promotes the formation of COPI vesicles, suggesting function as a component of the coat

Abstract: The role of GTPase-activating protein (GAP) that deactivates ADP-ribosylation factor 1 (ARF1) during the formation of coat protein I (COPI) vesicles has been unclear. GAP is originally thought to antagonize vesicle formation by triggering uncoating, but later studies suggest that GAP promotes cargo sorting, a process that occurs during vesicle formation. Recent models have attempted to reconcile these seemingly contradictory roles by suggesting that cargo proteins suppress GAP activity during vesicle formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
223
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(247 citation statements)
references
References 49 publications
22
223
1
Order By: Relevance
“…While our results contrast with previously reported results 18,28,29,34,35,39,58 in which it was reported that Arf1 and coatomer were sufficient for vesicle formation, they do not necessarily contradict these studies. The population of LUVs generated by the extrusion method, which is a frequently used method that we used in this work, contains many vesicles with diameters between 30 and 150 nm.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…While our results contrast with previously reported results 18,28,29,34,35,39,58 in which it was reported that Arf1 and coatomer were sufficient for vesicle formation, they do not necessarily contradict these studies. The population of LUVs generated by the extrusion method, which is a frequently used method that we used in this work, contains many vesicles with diameters between 30 and 150 nm.…”
Section: Discussioncontrasting
confidence: 99%
“…It is possible that Arf1•GTPgS could slow coatomer polymerization, implying a mechanism in which release of Arf1•GTP is required to ensure that cargo associates with coatomer prior to coatomer polymerization. This interpretation is consistent with the results reported by Hsu and colleagues 35,36,68 in which they found that the [R50K] ArfGAP1 did not efficiently generate COPI vesicles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among those, Brefeldin-A ADP-ribosylated Substrate (BARS) (Yang et al 2005), endophilin (Yang et al 2006), and ArfGAP1 (Yang et al 2002) are thought to play a role in membrane scission and/or act as a coat component. Some of these functions have been challenged by more recent investigations (Gallop et al 2005;Beck et al 2009b).…”
Section: Additional Proteins Implicated In Copi Fissionmentioning
confidence: 99%